FACTORS INFLUENCING BEHAVIOUR TOWARD PARTICIPATION IN SUSTAINABLE GREEN EXERCISE: A CONCEPTUAL FRAMEWORK - Chantiran, Kanageswary; Samsudin, Norsuriani; Mohd Yasin, Nurul Hafizah; Nazir, Mohd Hakam (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Green exercise, defined as physical activities conducted in a natural environment, has attracted international interest due to its potential double benefits on human health and environmental well-being. In Malaysia, despite the rich natural resources and extensive efforts put forward by the government in encouraging active lifestyles among its people, participation in green exercises is reportedly low. The increasing rates of physical inactivity and non-communicable diseases press for an urgent need to understand the behavioural determinants that drive Malaysians to engage in outdoor physical activities. Drawing from the TPB, this research investigates how attitudes, subjective norms, perceived behavioural control, green knowledge, and intrinsic motivation influence behaviour in terms of participation in green exercise. Additionally, demographic factors will be tested as a moderator between green knowledge and behavioural participation. Accordingly, this paper aims to contribute theoretically to the existing TPB literature on green exercise and provide practical insights to policymakers, public health practitioners, and environmental planners. Results may inform targeted interventions, improved green infrastructure, and community-based programs for fostering healthier lifestyles and enhancing environmental stewardship among Malaysians.